Rekonsiliasi Pemikiran Nahdlatul Ulama dan Sayyid Quthb: Penafsiran Ayat-ayat Ukhuwwah dalam Upaya Menciptakan Negara Damai - Musthafa, Ahmad Hikam (Research and Development Institution, Darussalam Institute for Islamic Studies, 2021)
This research was conducted to find a solution to the disputes between the major Islamic groups in Indonesia, Nahdlatul 'Ulama (NU) and followers of radical ideologies that refer to the thoughts of Sayyid Qutb. It is widely known that NU has the concept of a trilogy of ukhuwwah, the concepts of unity that a Muslim must carry out, and Qutb, an activist with the Muslim Brotherhood organization who also has the root word, akhi or brother. Sayyid Qutb, with his book of commentaries, was able to hypnotize radical groups to ignite the spirit of jihad further, but this group seemed to have ignored the name of the ideology he was pursuing. Some interpretations seem to be forgotten and even covered by the religious spirit of Muslims. In his book of commentaries, Qutb's thoughts are the same and mutually support the concept of the NU trilogy of ukhuwwah that Qutb also wants a state full of unity, unity, peace and egalitarianism because according to him Islam is not present as coercion, but reconciles all human beings regardless of ethnicity, race, language, to belief (religion).